A Case Report of a 13-Year-Old Female Child with Acute Liver Failure, Hyperammonemia and Cerebral Edema Admitted in Pediatric Intensive Care Unit (Journal of Neonatal, Infant and Child Health Nursing, 2026)
Background: A rare but potentially fatal illness in children, Acute Liver Failure (ALF) is characterized by a fast decline in liver function that causes hepatic encephalopathy and coagulopathy. Cerebral oedema and hyperammonemia are significant side effects that raise morbidity and death. For positive results, early diagnosis and timely intensive care management are essential.Case Presentation: A 13-year-old girl who was hospitalized to the Pediatric Intensive Care Unit (PICU) with fever, vomiting, altered sensorium, jaundice, and decreased oral intake is the subject of this case study. Acute liver failure linked to hyperammonemia and cerebral oedema was discovered through clinical assessment and laboratory testing. The patient needed supportive care, oxygen therapy, N-acetylcysteine infusion, antibiotics, and close observation.Management and Outcome: Intravenous fluids, broad-spectrum antibiotics, N-acetylcysteine infusion, anti-edema treatments, nutritional assistance, and ongoing neurological monitoring were all used to treat the youngster. To assess liver and kidney function, a series of laboratory tests were conducted. Under comprehensive care, the patient showed steady clinical progress.Conclusion: Early detection of acute liver to avoid serious consequences, failure and prompt PICU care are crucial. Improved patient outcomes are mostly the result of diligent observation, multidisciplinary cooperation, and comprehensive nursing care.
Keywords: Acute Liver Failure; Cerebral Edema; Hyperammonemia; Hepatic Encephalopathy; Pediatric Intensive Care Unit; N-Acetylcysteine